2020
DOI: 10.1371/journal.pone.0235449
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of disease modifying drugs on peripheral blood B cell subsets: A cross sectional study in multiple sclerosis patients treated with interferon-β, glatiramer acetate, dimethyl fumarate, fingolimod or natalizumab

Abstract: Background Several disease modifying drugs (DMDs) have been approved for the treatment of multiple sclerosis (MS), however, little is known about their differential impact on peripheral blood (PB) B cell subsets. Methods We performed a cross sectional study on PB B cells in MS patients treated with interferon-β (n = 25), glatiramer acetate (n = 19), dimethyl fumarate (n = 15), fingolimod (n = 16) or natalizumab (n = 22), untreated MS patients (n = 20), and in patients with non-inflammatory neurological disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 45 publications
(65 reference statements)
2
39
0
Order By: Relevance
“…When exploring the ability of these cells to predict secondary autoimmunity at baseline, we found that this was not the case in patients treated previously with natalizumab, who mostly presented a lower percentage of plasmablasts. This agrees with previous data showing that natalizumab and no other disease modifying drugs diminish the percentages of plasmablasts in blood (14,15,24).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When exploring the ability of these cells to predict secondary autoimmunity at baseline, we found that this was not the case in patients treated previously with natalizumab, who mostly presented a lower percentage of plasmablasts. This agrees with previous data showing that natalizumab and no other disease modifying drugs diminish the percentages of plasmablasts in blood (14,15,24).…”
Section: Discussionsupporting
confidence: 93%
“…Fourteen out of 22 patients presenting AIAEs but only eight of the 35 AIAEs-patients had a percentage of PB/PC higher than 0.10 [Odds ratio (OR) 5.91, 95% CI 1.83-19.10, p=0.004, Figure 4A]. To improve the sensitivity of the assay, we next explored if the heterogeneity found in AIAEs group could be related to previous treatment, since it has been described that natalizumab diminishes the concentration of blood plasmablasts (13,14). We found that five of the eight AIAEs patients who presented a percentages of PB/PC at baseline <0,1%, received natalizumab as the last treatment prior to alemtuzumab.…”
Section: Flow Cytometry Analysesmentioning
confidence: 99%
“…As mentioned previously, MS has historically been considered a T-cell-mediated disease, but emerging evidence also supports a significant role for the B-cell compartment (Hauser et al, 2008;Hauser and Cree, 2020;Kemmerer et al, 2020). This is a very important distinction as a recent study evaluating the most commonly used DMTs, found that these drugs have differential effects on distinct B-cell subsets, with some inducing an expansion of potentially pathogenic subtypes (Kemmerer et al, 2020). A role for the B-cell compartment in MS pathogenesis has been increasingly supported by the recent studies demonstrating efficacy of anti-CD20 antibody-mediated B-cell depletion in patients with both RRMS and progressive disease (Florou et al, 2020).…”
Section: Autoimmune Neuroinflammatory Diseasementioning
confidence: 90%
“…With the rapid expansion of targeted immunotherapies, fully appreciating the contribution of distinct entities within the neuroinflammatory response to MS pathogenesis will be critical for the development of efficacious and individualized therapeutic strategies (Rotstein and Montalban, 2019). As mentioned previously, MS has historically been considered a T-cell-mediated disease, but emerging evidence also supports a significant role for the B-cell compartment (Hauser et al, 2008;Hauser and Cree, 2020;Kemmerer et al, 2020). This is a very important distinction as a recent study evaluating the most commonly used DMTs, found that these drugs have differential effects on distinct B-cell subsets, with some inducing an expansion of potentially pathogenic subtypes (Kemmerer et al, 2020).…”
Section: Autoimmune Neuroinflammatory Diseasementioning
confidence: 99%
“…Multiple sclerosis (MS) is a chronic, progressive, neuroinflammatory disease characterized by immune-mediated inflammation, demyelination, and axonal damage in the central nervous system (CNS) [1][2][3]. Neuromyelitis optica spectrum disorder (NMOSD) is an inflammatory autoimmune disease of the CNS, primarily affecting the optic nerves and the spinal cord, leading to blindness and paralysis [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%